2013
DOI: 10.1111/j.1526-4637.2012.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Acceptable Symptom State of Chronic Musculoskeletal Pain Measured on a Visual Analog Scale in Moroccan Patients

Abstract: Half of patients were satisfied of their disease state, while the PAccSS threshold of pain was unexpectedly high. This could be explained by an overestimation of the pain intensity or a Moroccan patients' high tolerance to pain. The main protective factors that contribute to achieving the PAccSS were high educational level, high socioeconomic status, higher functional status, and shorter term disease duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Apart from the minimal clinically important difference, it is also important to consider the patient acceptable symptomatic state (PASS) which provides the basis for determining whether the treatment enabled patients to achieve a satisfactory state and which may be a clinically relevant treatment target. In our study, we found that in both groups the average pain, measured using the VAS was 5 below points since the first session, which fulfils the PASS values determined in populations with similar sociocultural characteristics, 36 despite the fact that this value was found to be unexpectedly high (50 mm) when compared with other populations.…”
Section: Discussionsupporting
confidence: 83%
“…Apart from the minimal clinically important difference, it is also important to consider the patient acceptable symptomatic state (PASS) which provides the basis for determining whether the treatment enabled patients to achieve a satisfactory state and which may be a clinically relevant treatment target. In our study, we found that in both groups the average pain, measured using the VAS was 5 below points since the first session, which fulfils the PASS values determined in populations with similar sociocultural characteristics, 36 despite the fact that this value was found to be unexpectedly high (50 mm) when compared with other populations.…”
Section: Discussionsupporting
confidence: 83%
“…Patient expectations, adaptability, tolerability, education and economic factors may impact the response to these questions in different ways. Higher levels of education and higher socioeconomic status were found to be independently associated with the PASS response when the PASS response was compared to a visual analogue scale in patients with musculoskeletal pain [10]. Also, the cutoff threshold of the visual analogue scale for the PASS response has been variable in different populations even though the pain scores were similar in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This intensity is high compared with other studies but may be associated with the predominance of traumatic pain in our study where the pain is acute. The average was lower in chronic pain, being 44 + 23 mm for an average duration of 7.4 years [11]. In a decreasing frequency order, the five most prescribed analgesics in our study were: paracetamol in tablet form, paracetamol + codein in association in tablets and ketoprofen in its suppository, tablet or gel dosage forms.…”
Section: Discussionmentioning
confidence: 77%